Coordinated Control Can Deliver Synergies Across Multiple Rainwater Storages. Issue 2 (16th February 2022) - Xu, Wei D.; Burns, Matthew J.; Cherqui, Frédéric; Smith‐Miles, Kate; Fletcher, Tim D.
Abstract: Studies in Real−Time Control (RTC) Rainwater Harvesting Systems (RWH) have to date been limited to the control of single storages, leaving the potential benefits of operating multiple storages in a coordinated manner largely untested. In this study, we aimed to design an optimization‐based RTC strategy that can operate multiple storages in a coordinated manner to achieve multiple objectives. We modeled the long‐term performance of this coordinated approach (i.e., termed as coordinated control ) across a range of storage sizes and compared it with a strategy that optimized the operation of each storage individually, ignoring the state of other stores within the system. Our results show that coordinated control delivered a synergy benefit in achieving better baseflow restoration, with almost no detriment to the water supply and flood protection (overflow reduction) performance. The efficiency achieved through coordinated control allows large storages to compensate for smaller, underperforming systems, to achieve higher overall performance. Such a finding suggests a general control principle in building coordination among multiple storages, which can potentially be adapted to mitigate flooding risks, and also applied to other stormwater control measures. This also opens up a new opportunity for practitioners to construct a future "smart rainwater grid" using a network of distributed storages, in combination with centralized large storages, to manage urban stormwater in a range of contexts and for a range of environmental objectives. Plain Language Summary: "Smart tanks" based on Real−Time Control (RTC) technology is increasingly applied in rainwater harvesting systems to address water shortages, urban flooding and streams depleted of flow. However, most uses of this technology have been applied to single tanks, without testing the potential of a network controlled in a coordinated manner to better address the environmental problems. To understand the effect of such coordination, we designed a control strategy accordingly and modeled its performance using a customized model. We found that a network of smart tanks can, in most cases, deliver a synergy benefit in restoring streamflow compared to systems that only work on their own. More importantly, this coordination allows large tanks to compensate for smaller, underperforming tanks, to achieve higher overall performance. It suggests a general control principle in building coordination among multiple storages, which can potentially be adapted to mitigate flooding risks, and also applied to other stormwater control measures. It opens up a smart future for managing urban water in a range of contexts and for a range of environmental objectives. Key Points: Multiple rainwater storages can be operated in a coordinated manner by Real−Time Control (RTC) technology for multiple objectives This coordinated RTC delivers synergy benefits in restoring baseflow Large storages compensate for small underperforming storages within the network